ACTION RESEARCH TO IMPROVE SOLID WASTE MANAGEMENT IN KATANGA SLUM, KAWEMPE DIVISION KAMPALA DISTRICT. - Nkabura, Hubert; Nansiiro, Hellen; Seguya , Ronald; Onaba, Joel; Namata, Davinia; Nakivumbi, Teddy; Akech , Loy Dorothy; Ojao, Carl David; Nanyingi, Miisa (Student's Journal of Health Research Africa, 2024)
Aim This study aims to avail the knowledge and skills on proper solid waste management to the community members of the Katanga slum. Methods A qualitative participatory methodological approach was adopted for their study following the recognized steps of community entry. Initial data for problem identification was obtained using focus group discussions; transect walks, and key informant interviews. Results The researchers gathered data from the entire community of Katanga slum with all the primary, secondary, and tertiary stakeholders involved. The biggest percentage of respondents was from the residents of the Katanga Slum who contributed to 60% of the researchers’ study population, the local leaders of the slum who contributed to 30% of the study population, and then the tertiary stakeholders who contributed 10% of the study population. Conclusion The community identified and prioritized solid waste management. Lobbying was done to supplement the identified solutions using the resources available such as providing rubbish sacks, rakes, gloves, and compound brooms to enable community members to practice proper waste management. Monitoring and Evaluation of the activities was done during and after the implementation process. The community of Katanga slum was able to gain sufficient knowledge which led to appropriate waste collection, segregation, transportation, and disposal. The research team and participants from the community were able to learn from each other and develop problem-solving and leadership skills. Recommendation In the process of the implementation of the recommendation another rubbish skip was provided by KCCA and rubbish sacks were placed at every household for collection of rubbish. As part of the exit strategy, a sustainability plan was set to ensure that activities go on, even after the researchers’ exit from the community, and key people in conjunction with the community health committee will take the lead in further implementation of the activities.